2021
DOI: 10.1177/19458924211061990
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Use After Endoscopic Endonasal Transsphenoidal Surgery

Abstract: Background The literature on opiate use after endoscopic endonasal transsphenoidal surgery (EETS) is limited. Objective To determine the risk factors for higher opiate use following EETS and the quantity of opiates used after discharge. Methods A retrospective review of 144 patients undergoing EETS from July 2018 to July 2020 was conducted. Patient, tumor, and surgical factors were documented. Pain scores and medications used on postoperative days (POD) 0 and 1, and discharge prescriptions, were recorded. Opia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In a recent retrospective study, Wu et al. suggested that active smokers and patients with grade 3 intraoperative CSF leaks were also associated with higher opiate use, requiring an additional 37.1 morphine milligram equivalents (MME) and 36.7 MME, respectively, in their first postoperative day 20 . Only one of these studies, however, examined how well patients’ pain was controlled, and none assessed whether some opioid‐naive patients’ pain may be overtreated with opioids.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent retrospective study, Wu et al. suggested that active smokers and patients with grade 3 intraoperative CSF leaks were also associated with higher opiate use, requiring an additional 37.1 morphine milligram equivalents (MME) and 36.7 MME, respectively, in their first postoperative day 20 . Only one of these studies, however, examined how well patients’ pain was controlled, and none assessed whether some opioid‐naive patients’ pain may be overtreated with opioids.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al performed a retrospective review of 144 patients undergoing endoscopic endonasal transsphenoidal surgery, concluding that although opiate needs were higher compared to those undergoing endoscopic sinus surgery, the overall requirements were still low. 12 Independent risk factors associated with higher opiate use in the immediate postoperative period included smokers and grade 3 intraoperative cerebrospinal fluid leaks. Keeping in the realm of endoscopic skull base surgery, Xie and colleagues performed a systematic review in order to determine the accuracy of various tests for the diagnosis and localization of CSF rhinorrhea.…”
mentioning
confidence: 99%